Effects of advance exposure to an animated surgery-related picture book on preoperative anxiety and anesthesia induction in preschool children: a randomized controlled trial - Yanyan Yang; Mazhong Zhang; Ying Sun; Zhezhe Peng; Xiaosu Zheng; Jijian Zheng (BMC, 2022)
Abstract Background Our aim was to investigate whether early surgical preparation by reading an animated picture book about procedure-related events could reduce the preoperative anxiety in preschoolers. Methods 131 patients, aged 3-6 years and underwent elective minor surgery were randomized either to a control or a picture book group. Both groups received general information about surgery and anesthesia in pre-anesthesia clinic. Patients in study group also received a surgery-depicting picture book for them to read at home a week earlier before surgery. Child anxiety was evaluated with the modified Yale Preoperative Anxiety Scale Short Form in six observing time points before anesthesia induction, and the compliance of anesthesia induction was assessed with the Induction Compliance Checklist (ICC). Results There were significantly lower anxiety scores in picture book group than in control group at the time of ready for intravenous cannulation in operating room [51.9 (23.6) vs. 67.2 (22.0); mean difference 15.3; 95% confidence interval (CI) 6.4-24.1; P = 0.001] and at the time of pre-anesthesia visit [27.8 (7.6) vs. 33.2 (13.6); mean difference 5.3; 95%CI 0.93-9.8; P = 0.018]. No significant differences of anxiety levels were found between two groups at other observed time points: in the anesthesia outpatient clinic, in the holding area, at separation from parent to operating room (OR), and on entrance to OR (P = 0.584, 0.335, 0.228, 0.137, respectively). The percentage of children with poor induction compliance (i.e., ICC ≥ 6) was higher in control group compared with that in picture book group [38% vs.21%; odds ratio(95%CI): 0.78(0.61-0.99); P = 0.041]. Conclusions Home-reading an animated picture book to get familiar with the perioperative events earlier prior to surgery could effectively reduce the preoperative anxiety level and increase the compliance during the induction of anesthesia in preschool children. Trial registration ChiCTR2000033583, 06/06/2020 www.chictr.org.cn .